A STUDY ON THE ROLE OF EDUCATION ON WOMEN’S REPRODUCTIVE HEALTH IN DOLLANG VILLAGE, NONEY DISTRICT, MANIPUR - Khuraijam, Konika; Sekho, Lovelyhoi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The primary purpose of the study is to examines the role of education in influencing women’s reproductive health in Dollang Village, Noney District, Manipur. Method: A descriptive survey was conducted among 100 married women using a structured questionnaire incorporating elements from established reproductive and women’s autonomy scales. Descriptive and inferential statistics were applied to assess differences in reproductive health knowledge, attitudes, and practices by educational level. Results: Educated women demonstrated significantly higher reproductive health knowledge (M = 28.84 vs. 26.92; SD = 3.78 vs. 6.91; t = 1.72, p < 0.05) and more positive attitudes (M = 28.38 vs. 23.52; SD = 3.32 vs. 6.47; p < 0.001) than uneducated women. Although educated women reported better practices (t = 0.61, p = 0.26), the difference was not statistically significant. Overall reproductive health scores were significantly higher among educated women (M = 84.52 vs. 76.72; SD = 8.53 vs. 17.99; t = 2.77, p = 0.004). Conclusion: The findings of this study conclude that education significantly improves knowledge and attitudes, though its impact on practices remains limited.